DINAMIKA MASYARAKAT DAN BUDAYA DALAM PENDIDIKAN ISLAM - Drs. H Firdaus (Ash-Shahabah : Jurnal Pendidikan dan Studi Islam, 2016)
Society is a large or small group, consisting of some humans, who by or for itself concerned by groups and influence upon each other. Sociology is the science of society or science-Detention kemasya who study humans as a group or community members, (not as individuals regardless of class or community). "Culture" is the result of activities and the creation of the mind (intellect) of man, such as trust, art and customs. Islamic education is the formation of a Muslim personality. Closely related to the human culture, the relationship can not be separated. If one is separated from the others, they are gone form respectively. Society is a cultural container, as well as a pile of soil to grow a tree, if people take a sample of the human spirit as a culture and as a society. Every human being is no culture and no culture of its people. Both merupajan duumvirate, is what form the social expression of culture.